The Sustainability of External Imbalances in the European Periphery - Vassilis Monastiriotis; Cigdem Borke Tunali (London School of Economics and Political Science (LSE), European Institute, 2016)
High and persistent external imbalances have become a key concern in the global economy, particularly after the Global Financial Crisis. The issue is particularly pertinent in Europe, as it poses challenges not only for its economic cohesion but also for its political coherence and the viability of the European project at large. In this study we investigate the sustainability of external imbalances in 15 countries from what is increasingly seen as the European periphery over the period 2000-2012 using quartely data. We apply a range of methods and compare across them to obtain a comprehensive picture of the patterns characterising external imbalances in this area. We find that external imbalances are on the whole large and, despite some significant adjustments in the post-crisis period, they continue to follow paths that are possibly unsustainable. Our results show a higher likelihood of confirming sustainability when looking separately at the current account and the net foreign asset position than when looking jointly at the trade and capital accounts (and thus at the overall fiscal reaction function – Bohn, 2007). This suggests, albeit tentatively, problems and vulnerabilities that go beyond simple concerns about price competitiveness and the trade performance of the countries under study.
Keywords: 330; external imbalances; current account sustainability; European periphery; error correction